Urban expansion and the loss of potential crop yield in the North China Plain: implications for regional food security (1980–2020) - Sheng, Shuangqing; Huang, Jinchuan (Frontiers in Sustainable Food Systems, 2025)
The global food security landscape is increasingly precarious as climate change, geopolitical conflicts, and pandemics compound its complexity. Concurrently, rapid urbanization has precipitated widespread loss of agricultural land in the North China Plain, yet research on the spatiotemporal dynamics of this conversion process—and its specific impacts on agricultural production potential—remains limited. In this study, we employ multi-temporal land use data from the China Land Use/Cover Change (CNLUCC) dataset for the years 1980, 1990, 2000, 2010, and 2020, alongside 1980 agricultural production potential data, to examine land use changes in the North China Plain over the period 1980–2020. Our analysis centers on the pace and intensity of urban expansion within city boundaries, the consequent loss of agricultural land, and the resulting decline in agricultural production potential. Findings reveal that, during this period, agricultural land—the predominant land use type—has been increasingly converted to urban areas, directly accounting for a loss of 1.25 × 104 km2 of farmland, with approximately 78.91% of new urban developments established on former agricultural lands. Cities such as Beijing, Linyi, and Zhengzhou have experienced the most substantial direct losses of farmland. Moreover, the speed and intensity of urban expansion exhibit significant spatial variability, following a distinct “higher in the center, lower at the periphery” pattern in agricultural land consumption, alongside an overall upward trend in expansion intensity. Between 1980 and 2020, the region experienced an aggregate loss of 7.03 × 109 kg in food production, with spatial patterns indicating lower losses in the north and higher losses in the central and southern regions. Cities including Tangshan, Baoding, Beijing, and Zhumadian incurred the highest reductions in agricultural production potential, whereas cities such as Jiyuan and Chengde exhibited relatively lower losses. This study underscores the spatial disparities in agricultural land loss and production potential depletion driven by urban expansion in the North China Plain, offering critical insights for land use planning and the promotion of sustainable regional development.